Penerapan Model CLIS (Children Learning in Science) untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas IV SD - Usi Rochmawati; Arifin Muslim (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to improve students' science process skills through the children learning in the science model in class IV. This research method uses classroom action research. The CAR was carried out for 2 cycles, each consisting of 2 learning meetings with one friend and one learning implementation plan. The subject of this research is class IV SDN 1 Kritig totaling 21 students consisting of 11 female and 10 male students. This research data collection tool uses science process skills tests, student activity observation sheets, and teacher activity observation sheets. The results of this CAR show that learning using the children learning in the science model can improve science process skills in grade IV SDN 1 Kritig. Students experienced an increase in each cycle in the first cycle, obtaining a total score of 23.76 with an average of 2.97 poor criteria. In contrast, in the second cycle, they obtained a total score of 36.96 with an average of 4.62 obtaining very good criteria.